KARAKTERISTIK PENGUNJUNG OBJEK WISATA ALAM AIR TERJUN GURUNG SEPANGIN DI DUSUN LUBUK MANTUK DESA TERKUDAK KECAMATAN KALIS KABUPATEN KAPUAS HULU - Yanter, Yohanes Bobbie; Siahaan, Sarma; Latifah, Siti (Universitas Tanjungpura, 2024)
This study aims to identify the characteristics of visitors to the natural tourist attraction Air Terjun Gurung Sepangin as a basis for destination development. A descriptive survey method was employed using accidental sampling, involving 30 respondents interviewed directly during their visit. Data collected included origin, age, gender, education level, employment status, marital status, information sources, transportation mode, travel time, visit frequency, visit duration, and arrival method. The results indicate that most visitors originate from Putussibau City, are aged 17